Looking Neat on the Street. Aesthetic Labor in Public Parking Patrol - Dahl, Dorte Boesby (Nordic Journal of Working Life Studies, 2013)
Research on aesthetic labor has been confined to service encounters in private sector industries. Aesthetic labor theory is critical of the commercialism that drives management of service labor and points to the discrimination of employees on the grounds of their “looks” that this entails. Considering the common conception today of the public sector as a service provider, application of the theory of aesthetic labor is relevant to public sector service work. But the public sector has many other purposes and mechanisms than those pertaining to increased revenues that may influence the use of aesthetic labor. This paper analyzes the aesthetic labor of Danish parking attendants in an organizational ethnography. A change management process in this organization has applied the principles of aesthetic labor actively for the purposes of diversity and health and safety. The paper shows how managers apply aesthetic labor principles to promote health and safety and workforce diversity, but also that the use of aesthetics has ambivalent purposes. Aesthetic labor is not as unequivocally applied for commercial purposes as hitherto assumed.